Antimicrobial Activity of Essential Oil from Seeds of Carum carvi and Its Composition (Bangladesh Journal of Microbiology, 2010)
The essential oil of Carum carvi L. seeds was screened for its antimicrobial activity against ten pathogenic bacteria and six phytopathogenic fungi. The essential oil showed promising inhibitory activity against all the test bacteria, even at 2 ìl/disc. The minimum inhibitory concentration (MIC, 100-300 ppm) and minimum bactericidal concentration (MBC, 200-400 ppm) values of essential oil were determined. The antifungal screening of the essential oil showed 100% inhibition of radial mycelial growth of all the test fungi at 100 ppm. The MIC and minimum fungicidal concentration (MFC) values were found to vary from 50-300 ppm and 200-400 ppm respectively. The essential oil extracted by hydrodistillation from seeds of C. carvi was analyzed by gas chromatography-mass spectrometry (GC-MS). About 10 compounds had been identified in the seeds oils, accounting for more than 99.7% of the oils. The main components of the seeds oil were thymol (48.20%), o-cymene (19.29%), ϒ-terpinen (17.61%) and trimethylene dichloride (8.81%). Keywords: Antimicrobial activities; Carum carvi; Essential oil; GC-MS; ThymolDOI: http://dx.doi.org/10.3329/bjm.v25i2.4867 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 85-89